Mitochondrial disorders in neuromuscular pathology - S. V. Kotov; O. P. Sidorova; E. V. Borodataya (Нервно-мышечные болезни, 2019)
Introduction. With the advent of new drugs — analogues of mitochondrial metabolites, the widespread introduction into practice of research methods for assessing the function of mitochondria in patients with neurological pathology and other diseases becomes relevant.Study aim. To determine the change in the intracellular activity of mitochondrial enzymes (succinate dehydrogenase, α -glycerophosphate dehydrogenase, glutamate dehydrogenase, lactate dehydrogenase) in case of neuromuscular diseases.Materials and methods. We examined 74patients with neuromuscular diseases. The activity of 4 mitochondrial enzymes involved in carbohydrate metabolism (lactate dehydrogenase), amino acid metabolism (glutamate dehydrogenase), fatty acids (α -glycerophosphate dehydrogenase), and mitochondrial respiratory chain complex II (succinate dehydrogenase) was evaluated. For a cytochemical study of the activity of mitochondrial enzymes in peripheral blood lymphocytes, the method proposed by A.G.E. Pearse as modified by R.P. Narcissov.Results. The greatest changes were revealed in cases with myotonic dystrophy: statistically significant decreases in the average activity value of all studied enzymes (р <0.05).In cases with hereditary motor-sensory neuropathy of type I the activity of succinate dehydrogenase and glutamate dehydrogenase is reduced (р <0.05), in cases with type II there are deviations in the activity indicators of mitochondrial enzymes, more pronounced compared with type I, but not statistically significant (p >0.05). In patients with myasthenia gravis, a decrease in the activity of α -glycerophosphate dehydrogenase and glutamate dehydrogenase (p <0.05) was noted. Average values of succinate dehydrogenase and lactate dehydrogenase activity indicators were also reduced (p >0.05). In cases with Landusi-Dejerine myopathy the activity of succinate dehydrogenase, α -glycerophosphate dehydrogenase and glutamate dehydrogenase were reduced, of which only for α -glycerophosphate    dehydrogenase p <0.05. In the analysis of each case in groups of patients with the studied pathology, it was shown that in addition to patients with myotonic dystrophy, in which all patients decreased the activity of succinate dehydrogenase, α -glycerophosphate dehydrogenase and glutamate dehydrogenase, in other cases, in some patients, the studied enzyme activity did not change.Conclusion. There are methods for studying these metabolites in plasma. The activity of mitochondrial enzymes is also examined. In cases with neuromuscular diseases, there are violations of the mitochondria. Therefore, it is necessary to consider such patients as metabolic patients and prescribe metabolic, antioxidant therapy to them.